MOTIVASI KETERLIBATAN UMAT LINGKUNGAN SANTA AGNES PAROKI SANTA MARIA BLITAR DALAM KEGIATAN LINGKUNGAN - Veronika Letek Tukan; Don Bosco Karnan Ardijanto (Lembaga Penelitian STKIP Widya Yuwana, 2026)
The Catholics faithful who has baptized being called to be actively involved in the Christ mission by doing those five tasks of the Church’s missions. However, many Catholics faithful do not involve yet in the Church’s missions. The study aimed to analyze the motivation for involvement of the members of Santa Agnes Basic Christian Community at Santa Maria Parish, Blitar in the Church’s missions. The research applied a qualitative method, and the data was collected by using direct interview technique, then informan of the study selected using purposive sampling technique. The results of the study indicated that the members of Basic Christian Community of Santa Agnes have a high enthusiasm and motivation to participate in doing the Church’s missions. The main motivations which drive the members of Basic Christian Community of Santa Agnes to be actively involved in the Church’s missions are the personal awareness of the grace of God’s forgiveness and health, the support of both the family and the Christian Community members, and being motivated by the values of sacrament of baptism.